2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32727
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Identity in Pre-College Students: A Literature Review

Abstract: is currently a Ph.D. student in the Department of Engineering Education at The Ohio State University. She is currently advised by Dr. Rachel Kajfez, and is part of the RIME collaborative (https://u.osu.edu/rimetime). Her research interests include engineering identity development in K12 students, engineering education in informal settings, and women's experiences in the engineering field. Prior to coming to Ohio State, Abigail worked as a researcher at Battelle Memorial Institute in Columbus, OH. She holds a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The top two reasons indicate that this particular virtual challenge attracted students who had high awareness in STEM in general and were likely seeking an opportunity that would allow them to engage in creative problem solving, something they enjoy doing-associated with engineering identity [21,22]. Interestingly, students also indicated that they expected to learn from university faculty and experts by participating in this extracurricular activity.…”
Section: Instrumentsmentioning
confidence: 99%
“…The top two reasons indicate that this particular virtual challenge attracted students who had high awareness in STEM in general and were likely seeking an opportunity that would allow them to engage in creative problem solving, something they enjoy doing-associated with engineering identity [21,22]. Interestingly, students also indicated that they expected to learn from university faculty and experts by participating in this extracurricular activity.…”
Section: Instrumentsmentioning
confidence: 99%
“…The concept of identity is commonly framed around the concept of "the kind of person one is seeking to be and enact in the here and now" [46] and, in the context of students still defining future goals and career paths, can also be thought of in terms of a future time perspective considering the kind of person a student envisions becoming [47]. Development of a professional engineering identity has been tied to retention in the engineering field [48] and can be weaker for engineering students compared to other science majors [49]. Cultivating students' development of engineering identity is important to increasing participation rates in engineering by women and underrepresented minorities [50].…”
Section: Rationalementioning
confidence: 99%
“…It is generally accepted as an evidenced proposition that (1) early engagement, elementary through high school, in STEM practices and activities is critically important for encouraging post-secondary and career interest in STEM fields [1][2][3][4][5][6]. Another generally accepted proposition (2), is that girls and women, similar to other underrepresented groups, face barriers to participation [1].…”
Section: Introductionmentioning
confidence: 99%